A fast-charging graphite negative electrode material, a preparation method therefor, and an application thereof

CN122930908APending Publication Date: 2026-10-16BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510405610.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,利用强碱溶液的化学侵蚀方法不易控制、无法形成结构稳定的石墨颗粒,且造孔的深度和均匀性难以保证

Benefits of technology

[0038](1) The core-shell structure fast-charging graphite anode material provided by the present invention provides a fast channel for the passage of lithium ions through its porous graphite core, increases the lithium ion transport layer spacing, reduces the transport resistance, improves the fast-charging performance of graphite, and buffers the volume change of graphite during charge and discharge cycles; its outer amorphous carbon shell fills and coats the pores and surface of the porous graphite core, improves the structural stability of graphite particles, significantly promotes the rapid diffusion of lithium ions on its surface, and ultimately improves the dynamic performance and cycle stability of the anode material in lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930908A_ABST
    Figure CN122930908A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery materials, and relates to a fast-charging type graphite negative electrode material and a preparation method and application thereof.The fast-charging type graphite negative electrode material is of a core-shell structure, and comprises a porous graphite inner core and an amorphous carbon shell.The amorphous carbon shell is filled in and coated on the pores and surface of the porous graphite inner core, and the pores of the porous graphite inner core are formed by alkali metal etching.The fast-charging type graphite negative electrode material provided by the application improves the controllability and uniformity of the internal pores of the graphite particles by alkali metal etching, is beneficial to the diffusion, rapid embedding and rapid extraction of lithium ions, the amorphous carbon shell improves the structural stability of the graphite particles, and finally improves the kinetic performance and cycle stability of the negative electrode material in a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, and relates to a graphite anode material, particularly a fast-charging graphite anode material and its preparation method and application. Background Technology

[0002] Currently, with the rapid global adoption of electric vehicles, the market demand for fast-charging lithium-ion batteries that can improve user driving efficiency and experience is growing stronger. In the fast-charging process of lithium-ion batteries, the ion / electron transport path running through the electrodes plays a crucial role. However, traditional graphite anodes lack fast ion transport channels, encountering extremely high overpotentials during ultra-fast power output, leading to problems such as lithium dendrite growth, capacity decay, and safety issues.

[0003] In recent years, emerging multi-scale porous anodes have focused on constructing efficient ion transport channels at multiple scales, presenting opportunities for fast-charging anodes. The narrow interlayer space of graphite crystals (0.335 nm) results in a long diffusion distance for lithium ions, leading to significant diffusion resistance. Furthermore, high charging rates can cause the growth of lithium dendrites on the graphite surface. To improve the electrochemical performance of graphite, various modification methods have been employed during graphite preparation, including surface coating, secondary granulation, and hard carbon doping. While these modification methods improve the rate performance of graphite, they reduce battery life and energy density, and they do not increase the diffusion rate of lithium ions within the graphite particles. Since lithium ions insert and detach from the edges of the graphite layers, the larger the graphite crystal, the slower the rate at which lithium ions enter and leave the graphite.

[0004] CN114335460A discloses a fast-charging graphite composite material, comprising porous graphite and a solid electrolyte core, as well as an inorganic lithium salt, carbon nanotubes, and a remaining amorphous carbon shell. This invention fills the porous carbon body with a solid electrolyte and coats its outer surface; however, the solid-solid interface between the solid electrolyte and graphite is not conducive to lithium-ion conduction, and the shell composed of lithium salt, carbon nanotubes, and amorphous carbon cannot maintain the structural stability of the graphite during charging and discharging.

[0005] CN116525789A increases the Li storage capacity inside graphite particles by creating pores in the graphite precursor. + Space, increasing the Li inside the graphite particles + Diffusion channels reduce Li +The diffusion resistance is reduced; at the same time, hard carbon is filled and coated inside and on the surface of the graphite particles, giving them a rich conductive network, reducing system impedance and battery polarization, and improving the battery's conductivity and rate performance. However, the chemical etching method using strong alkaline solutions is difficult to control, cannot form structurally stable graphite particles, and the depth and uniformity of pore formation are difficult to guarantee.

[0006] CN115483371A prepared a porous graphite anode material for lithium-ion batteries with fast-charging performance using nickel acetate as a pore-forming agent. However, after etching, the graphite is difficult to maintain stability during long-term cycling, leading to problems such as capacity reduction and structural damage.

[0007] CN114784231A utilizes oxygen oxidation etching to obtain porous graphite with multiple channels, and then uses amorphous carbon to coat the surface of the porous graphite to obtain a graphite anode material that is conducive to fast charging. However, the oxidation etching method results in residual oxygen, which is not conducive to the battery's capacity utilization and the rapid passage of lithium ions, and the uniformity of the etched channels is poor.

[0008] Therefore, how to provide a fast-charging graphite anode material and its preparation method, improve the controllability and uniformity of the internal channels of graphite particles, enhance the structural stability of graphite particles, and thus improve the dynamic performance and cycle stability of the anode material in lithium-ion batteries has become an urgent problem to be solved by those skilled in the art. Summary of the Invention

[0009] The purpose of this invention is to provide a fast-charging graphite anode material, its preparation method and application. Alkali metal etching improves the controllability and uniformity of the internal channels of graphite particles, which is beneficial to the diffusion and rapid insertion and extraction of lithium ions. The amorphous carbon shell enhances the structural stability of graphite particles, ultimately improving the kinetic performance and cycle stability of the anode material in lithium-ion batteries.

[0010] To achieve this objective, the present invention adopts the following technical solution:

[0011] In a first aspect, the present invention provides a fast-charging graphite anode material, wherein the fast-charging graphite anode material has a core-shell structure, comprising a porous graphite core and an amorphous carbon shell, wherein the amorphous carbon shell fills and covers the channels and surface of the porous graphite core, and the channels of the porous graphite core are formed by alkali metal etching.

[0012] The core-shell structure fast-charging graphite anode material provided by this invention has a porous graphite core that provides a fast channel for lithium ions to pass through, increases the interlayer spacing of lithium ion transport, reduces transport resistance, improves the fast-charging performance of graphite, and buffers the volume change of graphite during charge-discharge cycles. Its outer amorphous carbon shell fills and coats the pores and surface of the porous graphite core, improves the structural stability of graphite particles, significantly promotes the rapid diffusion of lithium ions on its surface, and ultimately improves the kinetic performance and cycle stability of the anode material in lithium-ion batteries.

[0013] Furthermore, compared to traditional acid-base etching or oxygen etching, the alkali metal etching used in this invention can form uniform channels with controllable pore size and depth inside graphite particles, improving the controllability and uniformity of the internal channels of graphite particles, which is beneficial to the diffusion and rapid insertion and extraction of lithium ions, and further improving the rate performance of the battery.

[0014] Preferably, the alkali metal element used in the alkali metal etching includes any one or a combination of at least two of Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, or Pt.

[0015] Preferably, the alkali metal used in the alkali metal etching has an average particle size of 10-3000 nm.

[0016] Preferably, the mass of the porous graphite core is used as the calculation benchmark, and the mass ratio of the amorphous carbon shell is 1%-30%.

[0017] Preferably, the amorphous carbon shell is made of hard carbon and / or soft carbon.

[0018] Preferably, the carbon precursor of the amorphous carbon shell includes any one or a combination of at least two of the following: coal tar, coal pitch, petroleum pitch, phenolic resin, epoxy resin, furan resin, furfuryl alcohol resin, polyacrylonitrile, or sugar organic compounds.

[0019] Preferably, the average pore size of the porous graphite core is 10-3000 nm.

[0020] Preferably, the porous graphite core is made of artificial graphite and / or natural graphite.

[0021] Preferably, the D50 particle size of the fast-charging graphite anode material is 1-50 μm.

[0022] Secondly, the present invention provides a method for preparing a fast-charging graphite anode material as described in the first aspect, the method comprising the following steps:

[0023] (1) Calcine the graphite material loaded with alkali metal particles to obtain coarse etched graphite.

[0024] (2) Alkali metal dissolution was carried out by mixing oxidizing solution and coarse etched graphite to obtain porous graphite core;

[0025] (3) Amorphous carbon precursor and porous graphite core are mixed and fused together, and then calcined and carbonized to obtain fast-charging graphite anode material.

[0026] Preferably, the loading of alkali metal particles in step (1) is 0.001-5 wt%, with the mass of graphite material as the calculation basis.

[0027] Preferably, the calcination process in step (1) is carried out in a protective gas atmosphere, and the protective gas includes any one or a combination of at least two of nitrogen, helium or argon.

[0028] Preferably, the calcination treatment in step (1) is carried out at a temperature of 300-1500℃ for a time of 0.5-50h.

[0029] Preferably, the oxidizing solution in step (2) includes any one or a combination of at least two of hydrochloric acid solution, sulfuric acid solution or nitric acid solution.

[0030] Preferably, the concentration of the oxidizing solution in step (2) is 5-70 wt%.

[0031] Preferably, the mass ratio of the amorphous carbon precursor and the porous graphite core in step (3) is (0.5-50):100.

[0032] Preferably, the rotation speed of the fusion coating in step (3) is 20-2000 rpm and the time is 1-720 min.

[0033] Preferably, the calcination and carbonization in step (3) is carried out in a protective gas atmosphere, and the protective gas includes any one or a combination of at least two of nitrogen, helium or argon.

[0034] Preferably, the calcination and carbonization temperature in step (3) is 300-1500℃ and the time is 0.5-50h.

[0035] Thirdly, the present invention provides a battery device comprising the fast-charging graphite anode material as described in the first aspect.

[0036] Fourthly, the present invention provides a vehicle comprising a fast-charging graphite anode material as described in the first aspect or a battery device as described in the third aspect.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The core-shell structure fast-charging graphite anode material provided by the present invention provides a fast channel for the passage of lithium ions through its porous graphite core, increases the lithium ion transport layer spacing, reduces the transport resistance, improves the fast-charging performance of graphite, and buffers the volume change of graphite during charge and discharge cycles; its outer amorphous carbon shell fills and coats the pores and surface of the porous graphite core, improves the structural stability of graphite particles, significantly promotes the rapid diffusion of lithium ions on its surface, and ultimately improves the dynamic performance and cycle stability of the anode material in lithium-ion batteries.

[0039] (2) Compared with traditional acid-base etching or oxygen etching, the alkali metal etching used in this invention can form uniform channels with controllable pore size and depth inside the graphite particles, which improves the controllability and uniformity of the pores inside the graphite particles, which is conducive to the diffusion and rapid insertion and extraction of lithium ions, and further improves the rate performance of the battery. Attached Figure Description

[0040] Figure 1 This is a schematic diagram of the fast-charging graphite anode material preparation method provided by the present invention;

[0041] Figure 2 These are scanning electron microscope images of the graphite material used in the preparation method provided in Example 1;

[0042] Figure 3 These are scanning electron microscope images of the porous graphite cores obtained by the preparation method provided in Example 1;

[0043] Figure 4 This is a scanning electron microscope image of the fast-charging graphite anode material obtained by the preparation method provided in Example 1. Detailed Implementation

[0044] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0045] One embodiment of the present invention provides a fast-charging graphite anode material, wherein the fast-charging graphite anode material has a core-shell structure, including a porous graphite core and an amorphous carbon shell, wherein the amorphous carbon shell fills and covers the channels and surface of the porous graphite core, and the channels of the porous graphite core are formed by alkali metal etching.

[0046] The core-shell structure fast-charging graphite anode material provided by this invention has a porous graphite core that provides a fast channel for lithium ions to pass through, increases the interlayer spacing of lithium ion transport, reduces transport resistance, improves the fast-charging performance of graphite, and buffers the volume change of graphite during charge-discharge cycles. Its outer amorphous carbon shell fills and coats the pores and surface of the porous graphite core, improves the structural stability of graphite particles, significantly promotes the rapid diffusion of lithium ions on its surface, and ultimately improves the kinetic performance and cycle stability of the anode material in lithium-ion batteries.

[0047] Furthermore, compared to traditional acid-base etching or oxygen etching, the alkali metal etching used in this invention can form uniform channels with controllable pore size and depth inside graphite particles, improving the controllability and uniformity of the internal channels of graphite particles, which is beneficial to the diffusion and rapid insertion and extraction of lithium ions, and further improving the rate performance of the battery.

[0048] In some embodiments, the alkali metal etching uses any one or at least two combinations of alkali metal elements selected from Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, or Pt. Typical but non-limiting combinations include combinations of Ni and Cu, Cu and Fe, Fe and Co, Co and Mn, Mn and Mo, Mo and Ru, Ru and Au, or Au and Pt.

[0049] In some embodiments, the alkali metal etching uses an average alkali metal particle size of 10-3000 nm, such as 10 nm, 100 nm, 200 nm, 400 nm, 600 nm, 800 nm, 1000 nm, 1200 nm, 1400 nm, 1600 nm, 1800 nm, 2000 nm, 2200 nm, 2400 nm, 2600 nm, 2800 nm or 3000 nm, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0050] In this invention, the average particle size of the alkali metal determines the pore size range of the porous graphite core. If the average particle size is less than 10 nm, it is not conducive to the smooth passage of lithium ions in the channels; if the average particle size is greater than 3000 nm, it can easily cause a significant reduction in the energy density of the graphite material.

[0051] In some embodiments, the mass of the porous graphite core is used as the calculation basis, and the mass percentage of the amorphous carbon shell is 1%-30%, for example, it can be 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0052] In this invention, the mass percentage of the amorphous carbon shell is crucial for balancing the structural stability of the graphite particles and the compaction density of the anode material. If the mass percentage is less than 1%, the structural stability of the graphite particles is significantly reduced; if the mass percentage is greater than 30%, it will lead to a significant reduction in the compaction density of the anode material, thus adversely affecting the energy density of the battery.

[0053] In some embodiments, the amorphous carbon shell is made of hard carbon and / or soft carbon.

[0054] In some embodiments, the carbon precursor of the amorphous carbon shell includes any one or a combination of at least two of coal tar, coal pitch, petroleum pitch, phenolic resin, epoxy resin, furan resin, furfuryl alcohol resin, polyacrylonitrile, or saccharide organic compounds. Typical but non-limiting combinations include combinations of coal tar and coal pitch, coal pitch and petroleum pitch, petroleum pitch and phenolic resin, phenolic resin and epoxy resin, epoxy resin and furan resin, furan resin and furfuryl alcohol resin, furfuryl alcohol resin and polyacrylonitrile, or polyacrylonitrile and saccharide organic compounds.

[0055] In some embodiments, the average pore size of the porous graphite core is 10-3000 nm, for example, it can be 10 nm, 100 nm, 200 nm, 400 nm, 600 nm, 800 nm, 1000 nm, 1200 nm, 1400 nm, 1600 nm, 1800 nm, 2000 nm, 2200 nm, 2400 nm, 2600 nm, 2800 nm or 3000 nm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0056] In some embodiments, the porous graphite core is made of synthetic graphite and / or natural graphite.

[0057] In some embodiments, the D50 particle size of the fast-charging graphite anode material is 1-50 μm, for example, it can be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0058] One embodiment of the present invention also provides a method for preparing the fast-charging graphite anode material described in any of the above embodiments, the preparation method comprising the following steps:

[0059] (1) Calcine the graphite material loaded with alkali metal particles to obtain coarse etched graphite.

[0060] (2) Alkali metal dissolution was carried out by mixing oxidizing solution and coarse etched graphite to obtain porous graphite core;

[0061] (3) Amorphous carbon precursor and porous graphite core are mixed and fused together, and then calcined and carbonized to obtain fast-charging graphite anode material.

[0062] In this invention, the method of loading alkali metal particles onto graphite material in step (1) is a conventional technique in the field. For example, it can be a sequential process of impregnation with a metal salt solution and reduction calcination. The metal salt can be an organic salt and / or an inorganic salt of an alkali metal element. As long as the loading of alkali metal particles can be achieved, no specific loading process is specified here.

[0063] In some embodiments, the mass of the graphite material is used as the calculation basis, and the loading of the alkali metal particles in step (1) is 0.001-5 wt%, for example, it can be 0.001 wt%, 0.01 wt%, 0.1 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, or 5 wt%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0064] In some embodiments, the calcination process in step (1) is carried out in a protective gas atmosphere, and the protective gas includes any one or at least two of nitrogen, helium or argon, with typical but non-limiting combinations including a combination of nitrogen and helium, a combination of helium and argon, a combination of nitrogen and argon, or a combination of nitrogen, helium and argon.

[0065] In some embodiments, the calcination temperature in step (1) is 300-1500℃, for example, it can be 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃ or 1500℃, and the time is 0.5-50h, for example, it can be 0.5h, 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h or 50h, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0066] In some embodiments, the oxidizing solution in step (2) includes any one or a combination of at least two of hydrochloric acid solution, sulfuric acid solution or nitric acid solution. Typical but non-limiting combinations include a combination of hydrochloric acid solution and sulfuric acid solution, a combination of sulfuric acid solution and nitric acid solution, a combination of hydrochloric acid solution and nitric acid solution, or a combination of hydrochloric acid solution, sulfuric acid solution and nitric acid solution.

[0067] In some embodiments, the concentration of the oxidizing solution in step (2) is 5-70 wt%, for example, it can be 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, or 70 wt%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0068] In some embodiments, the mixing mass ratio of the amorphous carbon precursor and the porous graphite core in step (3) is (0.5-50):100, for example, it can be 0.5:100, 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100 or 50:100, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0069] In some embodiments, the rotation speed of the fusion coating in step (3) is 20-2000 rpm, for example, it can be 20 rpm, 200 rpm, 400 rpm, 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm or 2000 rpm, and the time is 1-720 min, for example, it can be 1 min, 50 min, 100 min, 150 min, 200 min, 250 min, 300 min, 350 min, 400 min, 450 min, 500 min, 550 min, 600 min, 650 min, 700 min or 720 min, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0070] In some embodiments, the calcination carbonization in step (3) is carried out in a protective gas atmosphere, and the protective gas includes any one or at least two of nitrogen, helium or argon. Typical but non-limiting combinations include a combination of nitrogen and helium, a combination of helium and argon, a combination of nitrogen and argon, or a combination of nitrogen, helium and argon.

[0071] In some embodiments, the calcination and carbonization temperature in step (3) is 300-1500℃, for example, it can be 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃ or 1500℃, and the time is 0.5-50h, for example, it can be 0.5h, 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h or 50h, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0072] One embodiment of the present invention also provides a battery device comprising the fast-charging graphite anode material described in any of the above embodiments.

[0073] One embodiment of the present invention also provides a vehicle comprising the fast-charging graphite anode material or the battery device described in any of the above embodiments.

[0074] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0075] Example 1

[0076] This embodiment provides a fast-charging graphite anode material and its preparation method, such as... Figure 1 As shown, the preparation method includes the following steps:

[0077] (1) Artificial graphite loaded with Ni nanoparticles (particle size 500 nm, loading amount 0.1 wt%) (microstructure shown in [reference]) Figure 2 The graphite was placed in a nitrogen atmosphere and calcined at a temperature of 500°C for 12 hours. After natural cooling, it was washed with deionized water and dried to obtain coarse etched graphite.

[0078] (2) A 20wt% dilute sulfuric acid solution was mixed with the coarse etched graphite obtained in step (1) to dissolve alkali metals, and the solid-liquid ratio was controlled to be 0.05 g / mL. Then, the mixture was washed with deionized water and dried to obtain a porous graphite core (microscopic morphology see...). Figure 3 );

[0079] (3) Stir the petroleum asphalt and the porous graphite core obtained in step (2) in a mixer and control the mixing mass ratio of petroleum asphalt and porous graphite core to be 12:100. Then transfer the resulting mixture into a fusion machine and perform fusion coating at 200 rpm for 30 min to obtain the fusion product.

[0080] (4) The fusion obtained in step (3) was placed in a nitrogen atmosphere for calcination and carbonization, and the calcination and carbonization temperature was controlled at 1000℃ for 10h. After cooling to room temperature, a fast-charging graphite anode material was obtained (see microstructure). Figure 4 ).

[0081] like Figure 1 As shown, the fast-charging graphite anode material prepared by the above method has a core-shell structure, including a porous graphite core and an amorphous carbon shell, wherein the amorphous carbon shell fills and covers the pores and surface of the porous graphite core.

[0082] Testing revealed that the D50 particle size of the fast-charging graphite anode material obtained in this embodiment is 9 μm, and the average pore size of the porous graphite core is 500 nm. Using the mass of the porous graphite core as the calculation benchmark, the mass ratio of the amorphous carbon shell is 10%.

[0083] Example 2

[0084] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for replacing the Ni nanoparticles in step (1) with Ag nanoparticles of equal size and load, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.

[0085] Example 3

[0086] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for replacing the Ni nanoparticles in step (1) with Fe nanoparticles of equal size and load, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.

[0087] Example 4

[0088] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for replacing the artificial graphite in step (1) with natural graphite, the other steps and conditions are the same as in embodiment 1, so they will not be repeated here.

[0089] Example 5

[0090] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for replacing the petroleum pitch in step (3) with an equal mass of coal tar, the other steps and conditions are the same as in embodiment 1, so they will not be described in detail here.

[0091] Example 6

[0092] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for replacing the petroleum asphalt in step (3) with an equal mass of phenolic resin (molecular weight of 1200), the other steps and conditions are the same as in Example 1, so they will not be described in detail here.

[0093] Example 7

[0094] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for changing the particle size of the Ni nanoparticles in step (1) to 10 nm, so that the average pore size of the obtained porous graphite core is 10 nm, the other steps and conditions are the same as in Example 1, so they will not be repeated here.

[0095] Example 8

[0096] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for changing the particle size of the Ni nanoparticles in step (1) to 3 μm, so that the average pore size of the obtained porous graphite core is 3 μm, the other steps and conditions are the same as in Example 1, so they will not be repeated here.

[0097] Example 9

[0098] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for adjusting the D50 particle size of the obtained fast-charging graphite anode material to 1 μm by controlling the output particle size of the fusion machine, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.

[0099] Example 10

[0100] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for adjusting the D50 particle size of the obtained fast-charging graphite anode material to 50μm by controlling the output particle size of the fusion machine, the other steps and conditions are the same as in Example 1, so they will not be described in detail here.

[0101] Example 11

[0102] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for changing the mixing mass ratio of petroleum asphalt and porous graphite core in step (3) to 1.8:100, and changing the mass ratio of the resulting amorphous carbon shell to 1% of the mass of the porous graphite core, the other steps and conditions are the same as in Example 1, so they will not be repeated here.

[0103] Example 12

[0104] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for changing the mixing mass ratio of petroleum asphalt and porous graphite core in step (3) to 33:100, and changing the mass ratio of the resulting amorphous carbon shell to 30% of the mass of the porous graphite core, the other steps and conditions are the same as in Example 1, so they will not be repeated here.

[0105] Example 13

[0106] This embodiment provides a fast-charging graphite anode material and its preparation method. Except for changing the mixing mass ratio of petroleum asphalt and porous graphite core in step (3) to 56:100, and changing the mass ratio of the resulting amorphous carbon shell to 50% of the mass of the porous graphite core, the other steps and conditions are the same as in Example 1, so they will not be repeated here.

[0107] Comparative Example 1

[0108] This comparative example provides a graphite anode material and its preparation method, the preparation method comprising the following steps:

[0109] (1) Artificial graphite loaded with Ni nanoparticles (particle size of 500 nm and loading amount of 0.1 wt%) was placed in a nitrogen atmosphere for calcination treatment, and the calcination treatment temperature was controlled at 500 °C for 12 h. After natural cooling, it was washed with deionized water and dried in sequence to obtain coarse etched graphite.

[0110] (2) A 20wt% dilute sulfuric acid solution and the coarse etched graphite obtained in step (1) were mixed to dissolve alkali metals, and the solid-liquid ratio was controlled to be 0.05g / mL. Then, the mixture was washed with deionized water and dried to obtain a porous graphite core as a graphite anode material. The D50 particle size of the obtained graphite anode material was 9μm and the average pore size was 500nm.

[0111] Comparative Example 2

[0112] This comparative example provides a graphite anode material and its preparation method, the preparation method comprising the following steps:

[0113] (1) Artificial graphite was placed in a nitrogen atmosphere for calcination treatment, and the calcination temperature was controlled at 500℃ for 12h. After natural cooling, it was washed with deionized water and dried in sequence to obtain porous graphite.

[0114] (2) Stir the petroleum asphalt and the porous graphite obtained in step (1) in a mixer and control the mixing mass ratio of petroleum asphalt and porous graphite to be 12:100. Then transfer the resulting mixture into a fusion machine and perform fusion coating at 200 rpm for 30 min to obtain the fusion product.

[0115] (3) The fusion obtained in step (2) is placed in a nitrogen atmosphere for calcination and carbonization, and the calcination and carbonization temperature is controlled at 1000℃ for 10h. After cooling to room temperature, a graphite anode material is obtained.

[0116] The D50 particle size of the graphite anode material obtained in this comparative example is 9 μm, and the average pore size of the porous graphite is 500 nm. Based on the mass of the porous graphite, the mass ratio of the amorphous carbon shell is 10%.

[0117] Performance testing

[0118] (A) Button cells were prepared using the graphite anode materials obtained in Examples 1-13 and Comparative Examples 1-2, respectively, under the following conditions: anode active material content of 93.2 wt% and areal density of 8.5 mg / cm³. 2 Compacted density 1.5 g / cm³ 3 The positive electrode active material, LiFePO4, contains 97 wt% and has an areal density of 18.9 mg / cm³. 2 Compacted density 2.6 g / cm³ 3 The electrolyte was 1M LiPF6, the solvent was EC:EMC:DMC = 1:1:1, and 1wt% FEC and 1wt% VC were added. The first-efficiency, specific capacity and 4C capacity of each group of coin cells were examined. The relevant test results are shown in Table 1 below.

[0119] Table 1

[0120] button cell battery First effect <![CDATA[Specific capacity (mAh g -1 )]]> <![CDATA[4C Capacity Utilization (mAh g -1 )]]> Example 1 93.25% 356.62 304.24 Example 2 91.58% 355.73 301.85 Example 3 90.02% 350.54 303.15 Example 4 89.57% 354.73 299.65 Example 5 90.25% 353.45 291.46 Example 6 91.62% 354.98 286.54 Example 7 90.66% 352.15 301.46 Example 8 92.02% 351.11 300.54 Example 9 88.75% 350.13 292.48 Example 10 90.12% 348.88 288.95 Example 11 87.97% 351.35 294.15 Example 12 89.65% 346.73 286.48 Example 13 87.26% 340.73 274.63 Comparative Example 1 88.59% 345.73 296.72 Comparative Example 2 91.45% 350.24 204.25

[0121] (B) Soft-pack batteries were prepared using the graphite anode materials obtained in Examples 1-13 and Comparative Examples 1-2, respectively, under the following conditions: anode active material content of 93.2 wt% and areal density of 8.5 mg / cm³. 2 Compacted density 1.5 g / cm³ 3 The electrolyte was 1M LiPF6, the solvent was EC:EMC:DMC = 1:1:1, and 1wt% FEC and 1wt% VC were added. The first efficiency, capacity, DCR and 4C capacity of each group of soft-pack batteries were examined. The relevant test results are shown in Table 2 below.

[0122] Table 2

[0123]

[0124]

[0125] Therefore, the core-shell structure fast-charging graphite anode material provided by this invention provides a rapid channel for the passage of lithium ions through its porous graphite core, increases the interlayer spacing of lithium ion transport, reduces transport resistance, improves the fast-charging performance of graphite, and buffers the volume change of graphite during charge-discharge cycles. Its outer amorphous carbon shell fills and coats the pores and surface of the porous graphite core, enhances the structural stability of graphite particles, significantly promotes the rapid diffusion of lithium ions on its surface, and ultimately improves the kinetic performance and cycle stability of the anode material in lithium-ion batteries.

[0126] Furthermore, the alkali metal etching method used in this invention can form uniform channels with controllable pore size and depth inside graphite particles, improving the controllability and uniformity of the internal channels of graphite particles, which is beneficial to the diffusion and rapid insertion and extraction of lithium ions, and further improving the rate performance of the battery.

[0127] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A fast-charging graphite anode material, characterized in that, The fast-charging graphite anode material has a core-shell structure, including a porous graphite core and an amorphous carbon shell. The amorphous carbon shell fills and covers the channels and surface of the porous graphite core, and the channels of the porous graphite core are formed by alkali metal etching.

2. The fast-charging graphite anode material according to claim 1, characterized in that, The alkali metal elements used in the alkali metal etching include any one or a combination of at least two of Ni, Cu, Fe, Co, Mn, Mo, Ru, Au, or Pt. And / or, the alkali metal etching uses an average alkali metal particle size of 10-3000 nm.

3. The fast-charging graphite anode material according to claim 1 or 2, characterized in that, Using the mass of the porous graphite core as the calculation benchmark, the mass percentage of the amorphous carbon shell is 1%-30%. And / or, the material of the amorphous carbon shell includes hard carbon and / or soft carbon; And / or, the carbon precursor of the amorphous carbon shell includes any one or a combination of at least two of the following: coal tar, coal pitch, petroleum pitch, phenolic resin, epoxy resin, furan resin, furfuryl alcohol resin, polyacrylonitrile, or saccharide organic compounds.

4. The fast-charging graphite anode material according to claim 1 or 2, characterized in that, The average pore size of the porous graphite core is 10-3000 nm; And / or, the porous graphite core is made of artificial graphite and / or natural graphite; And / or, the D50 particle size of the fast-charging graphite anode material is 1-50 μm.

5. A method for preparing a fast-charging graphite anode material as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: (1) Calcine the graphite material loaded with alkali metal particles to obtain coarse etched graphite. (2) Alkali metal dissolution was carried out by mixing oxidizing solution and coarse etched graphite to obtain porous graphite core; (3) Amorphous carbon precursor and porous graphite core are mixed and fused together, and then calcined and carbonized to obtain fast-charging graphite anode material.

6. The preparation method according to claim 5, characterized in that, Using the mass of graphite material as the calculation basis, the loading of alkali metal particles in step (1) is 0.001-5 wt%. And / or, the calcination process in step (1) is carried out in a protective gas atmosphere, and the protective gas includes any one or a combination of at least two of nitrogen, helium or argon; And / or, the calcination treatment in step (1) is carried out at a temperature of 300-1500℃ for a time of 0.5-50h.

7. The preparation method according to claim 5, characterized in that, The oxidizing solution in step (2) includes any one or a combination of at least two of hydrochloric acid solution, sulfuric acid solution, or nitric acid solution; And / or, the concentration of the oxidizing solution in step (2) is 5-70 wt%.

8. The preparation method according to claim 5, characterized in that, The mass ratio of the amorphous carbon precursor and the porous graphite core in step (3) is (0.5-50):100; And / or, the rotation speed of the fusion coating in step (3) is 20-2000 rpm, and the time is 1-720 min; And / or, the calcination carbonization in step (3) is carried out in a protective gas atmosphere, and the protective gas includes any one or a combination of at least two of nitrogen, helium or argon; And / or, the calcination and carbonization temperature in step (3) is 300-1500℃ and the time is 0.5-50h.

9. A battery device, characterized in that, The battery device comprises the fast-charging graphite anode material as described in any one of claims 1-4.

10. A vehicle, characterized in that, The vehicle comprises a fast-charging graphite anode material as described in any one of claims 1-4 or a battery device as described in claim 9.

Citation Information

Patent Citations

  • Lithium-rich porous graphite material as well as preparation method and application thereof

    CN115483371A